Current Concepts in the Epidemiology, Diagnosis, and Management of Histoplasmosis Syndromes - Azar, Marwan M.; Loyd, James L.; Relich, Ryan F.; Wheat, L. Joseph; Hage, Chadi A. (Seminars in Respiratory and Critical Care Medicine, 2020)
Histoplasmosis is a global disease endemic to regions of all six inhabited continents. The areas of highest endemicity lie within the Mississippi and Ohio River Valleys of North America and parts of Central and South America. As a result of climate change and anthropogenic land utilization, the conditions suitable for Histoplasma capsulatum are changing, leading to a corresponding change in epidemiology. The clinical manifestations of histoplasmosis are protean, variably resembling other common conditions such as community-acquired pneumonia, tuberculosis, sarcoidosis, Crohn's disease, or malignancy. Making a successful diagnosis is contingent on a thorough understanding of epidemiology, common clinical presentations, and best testing practices for histoplasmosis. While most subclinical or self-limited diseases do not require treatment in immunocompetent patients, all immunocompromised patients and those with progressive disseminated disease or chronic pulmonary disease should be treated. Liposomal amphotericin B is the preferred agent for severe or disseminated disease, while itraconazole is adequate for milder cases and “step-down” therapy following response to amphotericin B. In this review, we discuss the current evidence-based approaches to the epidemiology, diagnosis, and management of histoplasmosis.
Keywords: histoplasmosis; pneumonia; disseminated; epidemiology; diagnosis; antigen; antibody; treatment